Synchronous and metachronous malignant gliomas: CT findings. - Van Tassel, P; Lee, Y Y; Bruner, J M (American Journal of Neuroradiology, 1988)
Twenty-one cases of malignant gliomas showing multiple tumor foci on CT are described. In 11 patients multiple lesions were evident on the initial CT scan (synchronous lesions); the other 10 patients developed one or more lesions months to years after the original gliomas (metachronous lesions) were documented. Distinctions between multifocal and multicentric gliomas are discussed and CT patterns presented. A diagnosis of synchronous multicentric or multifocal glioma should be considered in patients with multiple parenchymal masses and no known primary tumor elsewhere.